2022
DOI: 10.1186/s12889-022-12735-7
|View full text |Cite
|
Sign up to set email alerts
|

The risk of water, sanitation and hygiene on diarrhea-related infant mortality in eastern Ethiopia: a population-based nested case-control

Abstract: Background Diarrhea is still appeared to be as one of the leading global killers and disability-adjusted life-years lost, particularly in the infant and children. As per WHO, about 88% of diarrhea-related deaths are attributable to unsafe water, inadequate sanitation and insufficient hygiene, mainly in developing world. Thus, the main objective of this study was to find out the risk of such factors that contribute for diarrhea-related infant mortality in Eastern Ethiopia. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
(41 reference statements)
2
16
0
6
Order By: Relevance
“…The possible explanation for this is that good income is related to better hygiene, sanitation, and frequent use of health services. 5 , 14 , 16 , 19 This was also consistent with the study, which found that children from poor households were more prone to develop anemia when compared to children from the richest households. This is because, children from families with good economic status can get iron-rich foods such as animal foods and vitamin-rich foods, especially vitamins A and C, which are very important for iron absorption.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The possible explanation for this is that good income is related to better hygiene, sanitation, and frequent use of health services. 5 , 14 , 16 , 19 This was also consistent with the study, which found that children from poor households were more prone to develop anemia when compared to children from the richest households. This is because, children from families with good economic status can get iron-rich foods such as animal foods and vitamin-rich foods, especially vitamins A and C, which are very important for iron absorption.…”
Section: Discussionsupporting
confidence: 89%
“…This is also consistent with the study that found that, as the number of children increased, the quality of care by parents decreased, and as a result, it was expected that children were at risk for contamination. 14,19 This is also supported by a study that indicates a significant association between family size, low income, a low level of education, and the carelessness of care givers with anemia in children younger than five. 16 The findings of this study also indicated that children from larger families were more likely to develop environmental enteropathy.…”
Section: Discussionmentioning
confidence: 66%
“…The population-attributable fraction (PAF) of diarrheal disease due to risk factors such as inadequate drinking water, sanitation, and hygiene is more than 25% (WHO, 2022). Infants in households with improper management of liquid waste and hand-washing practices are at a greater risk of getting diarrhea-related infant death (Mebrahtom et al, 2022). Other studies reported about enhanced access to improved drinking water is associated with lower diarrhea prevalence, improved nutrition, and lower mortality in children under five years of age (Pickering et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sadly, despite the progress made globally, consumption of unsafe water exposes consumers to preventable health risks (WHO, 2022). Mebrahtom et al (2022) and WHO (2022) report that diarrhoea resulting from unsafe drinking-water is a leading killer annually across the world, especially for children under 5. Multiple risk factors have been identified as the cause of diarrhoea-related death, the factors include biological, social and environmental such as poor water supply, sanitation and hygiene (Mebrahtom et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Mebrahtom et al (2022) and WHO (2022) report that diarrhoea resulting from unsafe drinking-water is a leading killer annually across the world, especially for children under 5. Multiple risk factors have been identified as the cause of diarrhoea-related death, the factors include biological, social and environmental such as poor water supply, sanitation and hygiene (Mebrahtom et al, 2022). Therefore, accessing the risks associated with water supply systems could reduce the levels of risk consumers are exposed to.…”
Section: Introductionmentioning
confidence: 99%